Evaluating maternal and perinatal outcomes of eclampsia at a tertiary healthcare facility in Bihar, India: a retrospective study - Kumari, Priyanka; Swati; Kumar, Ashutosh; Gunjan, Gunjan (International Journal of Research in Medical Sciences, 2024)
Background: Eclampsia, characterized by seizures in women with preeclampsia, is a leading cause of mother and neonatal illness and death globally. Despite advancements in obstetric care, eclampsia remains a significant concern, especially in nations with poor and medium incomes. The aim of the study is to comprehensively assess the maternal and perinatal outcomes associated with eclampsia cases treated at a tertiary healthcare centre with the goal of improving understanding and management strategies for this serious medical condition. Methods: This retrospective observational study was conducted over 12 months. Data were collected from 200 eclampsia cases, focusing on demographic information, obstetric history, clinical characteristics, obstetric interventions, maternal complications, and perinatal outcomes. Statistical analysis was accomplished using SPSS version 21. Results: The mean age of patients was 28.5 years, with a majority (65%) being multiparous. Antepartum eclampsia was the most common clinical type (60%). Emergency caesarean section was performed in 70% of cases. Maternal complications included pulmonary edema (45%) and renal failure (25%), with a maternal mortality rate of 5%. Pre-term births occurred in 40% of cases, with an average gestational age at birth of 32 weeks. Additionally, 35% of newborns were low birth weight, and the perinatal mortality rate was 15%. Conclusions: This study highlights the substantial burden of neonatal and mother morbidity and death related with eclampsia in Bihar, India. Effective management strategies, including timely diagnosis, obstetric interventions, and preventive measures, are crucial in mitigating the adverse outcomes of eclampsia. Improving access to antenatal care, early detection of pre-eclampsia, and enhancing obstetric care services are essential in reducing the impact of eclampsia. Furthermore, continuous medical education programs for healthcare providers can enhance their knowledge and skills in managing eclampsia cases effectively.